Varicella in Poland: economic burden in children 1-12 years of age in Poland, 2010-2015 - Jacek Wysocki; Ilona Malecka; Joanna Stryczynska-Kazubska; Emmanouil Rampakakis; Barbara Kuter; Lara J. Wolfson (BMC, 2018)
Abstract Background The safety and efficacy of live-attenuated varicella zoster virus (VZV) vaccines in preventing varicella and reducing associated morbidity and mortality in real-world have been previously shown. In Poland, VZV vaccination is only mandatory for certain high-risk individuals. Here, we have conducted an evaluation of the clinical and economic burden of varicella in Poland. Methods Multicenter, retrospective chart review of varicella inpatients and outpatients aged 1-12 years with a primary diagnosis between 2010 and 2015. Varicella-related outcomes included the incidence of complications, the proportion of patients reporting healthcare resource utilization (HCRU), and frequency of HCRU. Direct costs were derived from per patient resource use multiplied by unit costs, and indirect costs were calculated as loss of revenue of caregivers reporting work days missed. The overall annual cost of varicella in Poland was estimated based on the calculated direct and indirect costs per case and the estimated number of varicella cases. All costs are presented in 2015 Polish złoty (PLN) / Euros (€). Results A total of 150 children with varicella were included, of which 75 were outpatients and 75 were inpatients with a mean (± SD) age of 3.9 (±2.6) and 4.2 (±2.3) years, respectively. Complications were experienced by 14.7% of outpatients and 82.7% of inpatients, of which the most common were skin and soft tissue infections and dehydration. The rate of HCRU was as follows: over-the-counter medications (80.0% outpatients, 81.3% inpatients), prescription medications (80.0% outpatients, 93.3% inpatients), tests/procedures (0.0% outpatients, 69.3% inpatients), and allied health professional consults (0.0% outpatients, 24.0% inpatients). Total (direct and indirect) cost per varicella case was 5013.3 PLN (€ 1198.1) for inpatients and 1027.2 PLN (€ 245.5) for outpatients, resulting in an estimated overall annual (2015) cost of varicella in Poland of 178,198,320 PLN (€ 42,588,385) among children aged 1-15 years. Conclusions Significant clinical and economic burden is associated with varicella in Poland. These results may be used to foster discussion related to the implications of implementing routine VZV vaccination in Poland.